(untitled) (Journal of Economic Research & Business Administration, 2016)
In this article the author considers the problem of implementation of the state employment policy at the local level. The notion of employment as a combination of economic and social relations associated with the provision of able-bodied citizens jobs and their participation in economic activities. The authors examined in detail the problems of unemployment and its specific features identified at the local level. Were also analyzed in detail the powers of local authorities to address the problems associated with employment. Were identified and analyzed for the management of local employment, which are currently very topical in view of the fact that in our country the legal regulation of employment is a matter of state and regional management. Local authorities in this matter have limited op portunities. In this regard, the conclusion, the authors proposed a range of measures to address the problems identified.